Back Cover: Synthesis of Hybrid Electroactive Materials by Low‐Potential Electropolymerization of Gold Nanoparticles Capped with Tailored EDOT‐Thiophene Precursor Units (ChemElectroChem 8/2014). Issue 8 (30th July 2014) - Yassin, Ali; Oçafrain, Maiténa; Blanchard, Philippe; Mallet, Romain; Roncali, Jean
<x xml:space="preserve">Abstract</x> On p. 1312, A. Yassin et al. show how electrochemical polymerization of gold nanoparticles decorated with a tailored thiophene‐3, 4‐ethylenedioxythiophene precursor leads to a homogeneous well‐defined electroactive hybrid material.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>